An investigation of the failure mechanisms in high temperature materials subjected to isothermal and anisothermal fatigue and creep conditions - Hyde, Christopher J.; Sun, Wei; Hyde, T.H. (Elsevier, 2011)
Many engineering components are subjected to conditions which have a detrimental effect on the materials from which they are made. Such components are used, for example, within high temperature regions of aeroengines (e.g. turbine discs) and power plant (e.g. steam pipes) and such conditions can include periods of isothermal and/or thermo-mechanical cyclic loading which may cause fatigue, excessive plasticity and creep. The combination of conditions to which the materials are subjected can have a strong influence on the failure mechanisms induced within the material.